MODEL PENGEMBANGAN BUDIDAYA RUMPUT LAUT Eucheuma Cottonii DI KECAMATAN BUMIRAYA KABUPATEN MOROWALI - Widyasari, Erviana Laili (JSTT, 2016)
This research, generally, aims at investigating the structure and the characteristic of model sytem in responding the potency of seaweed cultivation and formulating some alternative of policy in expanding seaweed cultivation to increase the cultivators prosperity and the local income. The validation test result to the model system of seaweed cultivation showed that the model was statiscally accepted. The test consisted of the Absolute Mean Error (AME) which P = 0,077 (P < 0.10), Absolute Variation Error (AVE) which P = 0.043 (P < 0.10), Durbin Watson (DW-test) which the value 1.92 and Kalman Filter (KF) which the value 0.313 (KF < 0.50). The Analysis Hierarchy Process (AHP) result showed that it is needed the expansion of seaweed cultivation which the feasibility value showed that B/C ratio is 2.67 and the number of priority vector is 0.45, it means that 45 % opinions support the expansion of seaweed cultivation in the investigating area. This case is also supported by the result of financial analysis, which the indicator value of B/C ratio is 1.15 and the IRR value is 79.06 %., it means that the business of seaweed cultivation is beneficial and suitable for it being expanded.